Deixis Used in Shang Chi and The Legend of The Ten Rings Movie Script - Ni Kadek Dinda Pratiwi; Ni Luh Sutjiati Beratha; Ni Wayan Sukarini (Stilistika : Journal of Indonesian Language and Literature, 2023)
This study is aimed to find out the types of deixis and analysis the function of deixis. Data were taken from Shang Chi and the Legend of the Ten Rings Movie Script. The theory that was applied in this study was proposed by Levinson. Documentation method and note-taking technique used in collecting the data. The collected data was analysed by using a descriptive qualitative method. Meanwhile, in presenting the data analysis, this study used an informal method. The result shows that all the types of deixis and its function based on the theory by Levinson are found in the data source.